Supersulfide controls intestinal inflammation by suppressing CD4+ T cell proliferation - Tayama, Shunichi; Kitamura, Yuya; Hiraide, Kyoga; Suzuki, Hibiki; Li, Jing; Yang, Ziying; Mitsuwaka, Ryoji; Kawajiri, Akihisa; Sato, Kosuke; Gao, Feng; Nakai, Taku; Okuyama, Yuko; et al. (Frontiers in Immunology, 2025)
Inflammatory bowel disease (IBD) is characterized by chronic intestinal inflammation where CD4+ T lymphocytes play an essential role. Accumulating evidence suggests that immune responses driven by CD4+ T cells are critically regulated by various metabolic pathways including oxidative phosphorylation and glycolysis. Here we show that CARS2/CPERS-dependent supersulfide metabolism restrains CD4+ T cell proliferation in a cell-intrinsic manner. Under steady state, Cars2+/- mice exhibited spontaneous accumulation of effector/memory CD4+ T cells in the colon with age. In lymphopenic conditions, Cars2+/- CD4+ T cells showed enhanced cell cycle entry with reduced expression of a cell cycle inhibitor Trp53 and triggered an exacerbated form of colitis, the response being rescued by treatment with a supersulfide donor glutathione trisulfide (GSSSG). Furthermore, re-analysis of publicly available gene datasets of human colonic CD4+ T lymphocytes revealed that downregulation of CARS2 was associated with pathogenesis of IBD, and indeed, addition of GSSSG inhibited human CD4+ T cell proliferation in vitro. Together these observations reveal that CARS2/CPERS-dependent supersulfide metabolism is essential for homeostasis of intestinal effector/memory CD4+ T cells, and further suggest that dysregulation of the same metabolic pathway can lead to development of gut inflammation both in mice and humans.